New England color : field techniques for great pictures - Zuckerman, Jim (Peachpit Press, 2010)
"Learn photography with master photographer Jim Zuckerman as he photographs New England in autumn. This area offers a variety of historic locations from the lighthouses of Maine to classic churches and cemeteries in Massachusetts. The fall foliage provides surprising splashes of color around every country road. In this photography video Jim shoots in a variety of lighting conditions, from sunrise to sunset, and is faced with the challenges every outdoor photographer encounters. With over 40 years experience as a professional photographer, Jim Zuckerman shares a wealth of photo tips, tricks, and experience from the field."--Resource description page.